The effects of mobile-assisted problem-based language learning on speaking proficiency of Iranian language learners in the second language / Loghman Ansarian - Loghman , Ansarian (2020)
Problem-Based Language Learning (PBLL) is a cognitive and collaborative approach to language learning which has gained attention of language educators in the last two decades. Although previous researches have revealed that PBLL is a promising approach to language learning, a detailed look at the effects of mobile-assisted PBLL on linguistic features of speaking proficiency of the learners and the learners' views with regard to this approach are absent. In an attempt to shed light on this issue, a confirmatory sequence mixed-methods study in the EFL context of Iran was conducted. The effects of mobile-assisted PBLL was compared to the conventional language learning approach. The experimental group (n=37) went through mobile-assisted PBLL instruction and the control group (n=33) went through conventional instruction. The PBLL model was designed based on Hmelo Silver's (2004) model and Hung's (2006) 3C3R model. The Oxford Placement Test (OPT) was administered as a placement test, IELTS speaking test (Parts 2 and 3) was once administered as the homogeneity test-pretest and 3 times as posttests. A semi-structured interview was also conducted twice, once at the middle and the other, at the end of the treatment with the experimental group participants (n=17). The results of multivariate ANOVA (MANOVA) analysis after 26 sessions of treatment revealed that PBLL can positively affect the participants' proficiency in terms of accuracy of grammatical structures, vocabulary, spoken fluency, and pronunciation; however, in terms of task achievement, no significant effect was found. In addition to this, it was found that the participants’ views with regard to mobile-assisted PBLL are mostly positive. The learners believed that this approach provides them with more practice in the form of monologues and dialogues to deal with real-life issues, and it also reveals their weaknesses to them. Furthermore, it increases their self-confidence, provides them with opportunities to check their pronunciation with peers in class and to compare them to valid online sources, which also affects their incidental vocabulary knowledge, their listening and speaking proficiency at the same time. This study can have pedagogical implications for curriculum designers, language teachers, material developers, and language test designers.